STEP 1- since 6 doesn't contain the variable to solve for move it to the right side of the equation by subtracting 6 from both sides
X^2-8X=-6
STEP 2- create a trinomial square on the left side of the equation find the value that is equal to the square of half of b the coefficient of x
(b/2)^2 =(-4)^2
STEP 3- add the term to each side of the equation
x^2-8x+(-4)^2=-6=(-4)
STEP 4- simplify the equation
x^2-8x+16=10
STEP 5- factor the perfect trinomial square into (x-4)^2
(x-4)^2=10
STEP 6-solve the equation for x
x=4= square root of 10
Answer:
15 equation: 195=105+6x
Step-by-step explanation:
he starts out with 105 and the rate of change is 6x so to get the answer u wanna make and equation (195=105+6x) then you would subtract the 105
195=105+6x
-105 -105
---------------------
90=0 +6x
then u would divide by 6
90/6=6x/6
x=15
Answer:
I plotted it out on the graph and here it is: